2007
DOI: 10.1097/00000542-200702000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Effective Reversal of Moderate Rocuronium- or Vecuronium-induced Neuromuscular Block with Sugammadex, a Selective Relaxant Binding Agent

Abstract: Sugammadex rapidly reversed rocuronium- or vecuronium-induced neuromuscular block at reappearance of the second muscle twitch and was well tolerated. A dose-response relation was observed with sugammadex for reversal of both rocuronium- and vecuronium-induced neuromuscular block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(112 citation statements)
references
References 15 publications
1
105
0
3
Order By: Relevance
“…Similar uncertainty remains regarding the ideal dosing of sugammadex, which would prevent residual curarization. While some studies [14] recommend dosing sugammadex at 2 mg.kg -1 total body weight if two twitches are present in the TOF count, Van Lanke [15] found that the appropriate dose should be calculated on the basis of ideal body weight according to the formula "Ideal body weight plus 40% of the excess weight". This means that though some of our patients were suboptimally dosed on a total body weight basis, they still received enough sugammadex according to Van Lanker's recommended dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Similar uncertainty remains regarding the ideal dosing of sugammadex, which would prevent residual curarization. While some studies [14] recommend dosing sugammadex at 2 mg.kg -1 total body weight if two twitches are present in the TOF count, Van Lanke [15] found that the appropriate dose should be calculated on the basis of ideal body weight according to the formula "Ideal body weight plus 40% of the excess weight". This means that though some of our patients were suboptimally dosed on a total body weight basis, they still received enough sugammadex according to Van Lanker's recommended dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of sugammadex have been established in various clinical trials [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Treatment options for sugammadex include rapid reversal at 3 min after rocuronium using 16 mg kg -1 sugammadex, deep blockade reversal using 4 mg kg -1 sugammadex administered at recovery to one or two post-tetanic counts or 15 min post 0.6 mg kg -1 rocuronium and moderate blockade reversal using 2 mg kg -1 at reappearance of the second twitch (T2) of the train-of-four (TOF) monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…13 Also, moderate (T 2 ) rocuronium-and vecuronium-induced neuromuscular blocks were successfully reversed under propofol-remifentanil anesthesia. 4 A multicenter study 9 demonstrated a clear dose-response relationship for the reversal of moderate rocuronium-and vecuronium-induced neuromuscular block with sugammadex 0.5, 1.0, 2.0, and 4.0 mg/kg under sevoflurane anesthesia. Recovery times to TOF ratio 0.9 were shorter in the rocuronium versus the vecuronium group, and the difference was the most pronounced at sugammadex 0.5 mg/kg.…”
mentioning
confidence: 99%